PSYCHOLOGICAL MECHANISMS OF CONSCIOUS REJECTION OF MOTHERHOOD - Тодорцева, Юлія; Арнаут, Олена (SWorldJournal, 2023)
The article includes an analysis of the results of empirical study to identify psychological mechanisms of voluntarily childless women in Ukraine, indicating the psychological mechanisms of women who consciously rejected motherhood.